Peningkatan Literasi dan Inklusi Green Banking pada Komunitas Remaja dan Anak-anak Rantau Warga Indonesia di Malaysia - Rahayu, Yayuk Sri; Sulistyowati, Sulistyowati; Fikriyah, Ashfa; Yasin, Achmad; Kharisma, Ikke (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This service aims to increase green banking literacy and inclusion in the community of Indonesian overseas youth and children in Malaysia. Using the ABCD (asset-based community development) method, this activity is focused on utilizing the potential and resources that exist in the community. The objectives of the service include increasing understanding of green banking principles, forming environmental awareness, and increasing the accessibility of sustainable banking services. Through a collaborative approach, it is hoped that the community can utilize new knowledge to support sustainable and environmentally friendly financial practices. The success of the service is measured based on increasing green banking literacy and active participation in sustainability initiatives in the community.